Development of an simplified modeling control system for maximization of polymerization in a pilot plant - Khan, M Jakir H; Rashid, Muhammad Mahbubur; Ferdaus, Mohammad Meftahul (IEEE, 2015)
Polymer is obtained by a process called polymerization which is actually a chemical reaction to combine monomer molecules together. In this work a suitable model and control system was proposed for obtaining the maximum production yield of industrial grade polymer. Significant process parameters specifically system temperature (0C), reaction pressure (bar), and raw materials ratio (%) were selected as process controlling inputs. Differential pressure (DP) obtained from a series of experiments were fitted into a quadratic polynomial model by applying multiple regression analysis. By analyzing the response of three dimensional surface plot, contour plot and soling the regression model equation, the optimal process conditions are obtained. To optimize the interactions among the quadratic polynomial models Center Composite Design (CCD) technique under RSM was used. The results showed the best conditions or the optimized values for initial temperature, system pressure to initiate reaction and monomer gas ratio. Further the maximum predicted value of DP was also obtained at same conditions. At last the trail experiments are evaluated by using the optimum conditions to achieve the higher DP.